Kuliah Kerja Nyata Tematik Periode Ke 1 Tahun 2025 Desa/Kelurahan Pematang Gubernur Kecamatan Muara Bangkahulu Kota Bengkulu - Pebriani, Emi; Qurratul A’yuni; Hasanah, Fikrah Mardatillah; Diokissti; Annisa Yulianti; Helta Nurwahyuni; Rahmawati, Diyah Tepi; Tuti Rohani; Danur Azissah (Utami Publisher, 2025)
This community service activity aims to conduct socialisation and counselling in efforts to prevent hypertension in RT.07 Pematang Governor Village, Muara Bangkahulu District. In this era there is a change in disease patterns. This is characterised by the increasing number of non-communicable diseases. Until now, hypertension is still one of the non-communicable diseases that is often known as the silent killer because in addition to its sudden appearance, this disease is also one of the diseases causing serious problems (Shaumi & Achmad, 2019). Based on the results of the most disease data at the Muara Bangkahulu Health Centre in 2024, hypertension is ranked second among the most common diseases suffered by the community with an estimated 1,452 people. The implementation of activities in collaboration with RT officials and the Muara Bangkahulu Puskesmas was carried out using socialisation and counseling methods.